2010
DOI: 10.2106/jbjs.i.01270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early and Delayed Mechanical Loading on Tendon-to-Bone Healing After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Modulation of the mechanical environment may profoundly affect the healing tendon graft-bone interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 32 publications
4
95
1
Order By: Relevance
“…However, neither group had significantly improved biomechanical or microstructural properties compared with the prolonged-immobilization group. While previous studies in our laboratory showed that the biomechanical properties of tendon-to-bone healing were better after delayed application of 2% axial strain than they were in the immediate-loading and immobilized groups 14 , the increase to 10% axial strain in the present study did not yield similar results. This suggests that the beneficial effects of delayed loading after a brief period of immobilization may have been offset by the detrimental effects of excessive graft-strain levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, neither group had significantly improved biomechanical or microstructural properties compared with the prolonged-immobilization group. While previous studies in our laboratory showed that the biomechanical properties of tendon-to-bone healing were better after delayed application of 2% axial strain than they were in the immediate-loading and immobilized groups 14 , the increase to 10% axial strain in the present study did not yield similar results. This suggests that the beneficial effects of delayed loading after a brief period of immobilization may have been offset by the detrimental effects of excessive graft-strain levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Seventy male Sprague-Dawley rats (weight range, 300 to 380 g; age, less than three months) underwent ACL reconstruction with a flexor digitorum longus autograft 14,16 . The knees were immobilized with an external fixator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this process, mechanical and biological factors are involved in the healing process of the reconstructed tendons [25][26][27][28][29]. In the distal part of the bone tunnel, the mechanical effect was relatively low and the graft-bone healing was influenced mainly by the biological environment.…”
Section: Discussionmentioning
confidence: 99%